2016
DOI: 10.1186/s12889-016-3225-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory study of the implications of research on the use of smart connected devices for prevention: a scoping review

Abstract: BackgroundSmart devices and mobile applications are now an integral part of all aspects of everyday life. They are particularly numerous in the field of health, contributing to the movement called ehealth. What is the potential role of these devices as prevention supports? The purpose of this article is to provide an exploratory analysis of the use, efficacy and contribution to conventional prevention strategies.MethodsTo address this issue, we conducted a scoping-review on the basis of 105 publications from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 79 publications
1
21
0
Order By: Relevance
“…). Allowing the research team to provide feedback to participants throughout the intervention also probably improved motivation by creating a supportive environment (Petit & Cambon, ). In addition, knowing the research team were monitoring exercise may have increased motivation to adhere to the programme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Allowing the research team to provide feedback to participants throughout the intervention also probably improved motivation by creating a supportive environment (Petit & Cambon, ). In addition, knowing the research team were monitoring exercise may have increased motivation to adhere to the programme.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in sedentary individuals has shown that immediate feedback illustrating HR can positivity influence participant motivation (Kinnafick et al 2018). Allowing the research team to provide feedback to participants throughout the intervention also probably improved motivation by creating a supportive environment (Petit & Cambon, 2016). In addition, knowing the research team were monitoring exercise may have increased motivation to adhere to the programme.…”
Section: Myocyte Adaptationsmentioning
confidence: 99%
“…Technologies such as activity monitors provide opportunities to enhance delivery of goal setting and feedback, allowing for more frequent and automatic feedback on progress towards activity goals, tailored updating of goals based on achievement and remote contact with intervention providers [ 23 ]. In addition to addressing psychological needs for competence, incorporation of social components may support motivation through promoting relatedness to other service users.…”
Section: Introductionmentioning
confidence: 99%
“…Several initiatives exist in regard to the use of technology in eldercare. Numerous technologies are promoted in eldercare (van Hoof et al 2011, Pritchard and Brittain 2015, Garmann-Johnsen and Eikebrokk 2017, Petit and Cambon 2016, Pols 2017, Peeters, Wiegers, and Friele 2013, including telehealth services, telecare, smart devices, monitoring technology, personal alarms, ambient living technology, and welfare technology (Hofmann 2013). All of these are said to enable a safer, healthier, and more active lifestyle for older people, thereby maximising their independence, quality of life, and well-being (Milligan, Roberts, andMort 2011, Sánchez, Taylor, andBing-Jonsson 2017).…”
Section: Introductionmentioning
confidence: 99%